INTERFAITH MARRIAGE IN THE PERSPECTIVE OF ISLAMIC LAW AND LEGISLATION: INTERFAITH MARRIAGE IN THE PERSPECTIVE OF ISLAMIC LAW AND LEGISLATION - bukhari, bukhari (Prodi Pengembangan Masyarakat Islam STAIN Teungku Dirundeng Meulaboh, 2022)
Ulama salaf does not allow Muslim men to marry non-Muslim women absolutely, and others allow marrying kitabiyah (people of the Book), namely Yahudi and Christian women In objective reality, marriage of different religions in Indonesia today has more negative effects than positive effects, such as the problem of family harmony and the future of child religiousness. Sometimes some speculate that the problem can be solved by cultivating tolerance and developing a